Ibn Asakir and early Islamic history - Lindsay, James E., 1957- (Berlin : Gerlach Press, 2021)
Ibn ʻAsākir's massive Taʼrīkh madīnat Dimashq (TMD) is a veritable gold mine of information for our understanding of the first five and one-half centuries of Islamic history. This book offers important insights on the mechanics of Arabic historiography, in particular on biographical sources from the Middle period. Moreover, two contributions show that Ibn ʻAsākir pursued a political and sectarian agenda within his TMD. 1. James E. Lindsay, Ibn ʻAsākir, His Taʼrīkh madīnat Dimashq and its Usefulness for Understanding Early Islamic History; 2. Suleiman A. Mourad, Jesus According to Ibn ʻAsākir
6. PAUL M. COBB, Community versus Contention: Ibn 'Asākir and 'Abbāsid Syria -- SULEIMAN A. MOURAD, Appendix A. Publication History of TMD -- Appendix B. Studies Addressing TMD -- Appendix C. Major Lacunae in TMD -- Appendix D. Pre-Islamic Sacred Biographies in TMD -- Appendix E. Muḥammad, the Rāshidūn, and the Umayyad Caliphs in TMD -- Index
eBooks on EBSCOhost
Keywords: Ibn ʻAsākir, ʻAlī ibn al-Ḥasan, -- 1105-1176.; Tārīkh madīnat Dimashq (Ibn ʻAsākir, ʻAlī ibn al-Ḥasan); Historiography -- Syria; Biography -- Middle Ages, 500-1500.; Damascus (Syria) -- History -- Early works to 1800.; Syria -- Historiography; Biographies -- 500-1500 (Moyen Âge); Historiographie -- Syrie; Biography -- Middle Ages; Historiography; Syria; Syria -- Damascus; 500-1500; Early works; History